2021
DOI: 10.11646/zootaxa.4942.4.2
|View full text |Cite
|
Sign up to set email alerts
|

On some modern Ostracoda (Crustacea) from the Tibetan Plateau in SW China, with descriptions of three new species

Abstract: Studies of Holocene ostracods of the Tibetan Plateau have mostly centred around valves and carapaces collected from lake sediments, some at or near the substrate surface and others from short cores. Reports from habitats other than lakes are scarce, and few living species found in this region have appendages described, hindering further taxonomic and phylogenetic work. For this study collections of living ostracods were made in mostly ponds, as well as two rivers and one lake. Six species, including three prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 978 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Yu et al (2009) suggested that the number of Chinese endemic species should represent ~ 40% of the entire ostracods (including subfossil species) of this country. However, with the increasing knowledge on the extant non-marine ostracods of China (Kong et al 2014;Zhai and Zhao 2014;Yu 2018, 2020;Peng et al 2021), the ratio of endemic species seems to be declining. Among all the ostracods listed in The three new species also add to our knowledge on the geographical distribution of extant ostracods in general.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Yu et al (2009) suggested that the number of Chinese endemic species should represent ~ 40% of the entire ostracods (including subfossil species) of this country. However, with the increasing knowledge on the extant non-marine ostracods of China (Kong et al 2014;Zhai and Zhao 2014;Yu 2018, 2020;Peng et al 2021), the ratio of endemic species seems to be declining. Among all the ostracods listed in The three new species also add to our knowledge on the geographical distribution of extant ostracods in general.…”
Section: Discussionmentioning
confidence: 99%
“… Yu et al (2009) suggested that the number of Chinese endemic species should represent ~ 40% of the entire ostracods (including subfossil species) of this country. However, with the increasing knowledge on the extant non-marine ostracods of China ( Kong et al 2014 ; Zhai and Zhao 2014 ; Ma and Yu 2018 , 2020 ; Peng et al 2021 ), the ratio of endemic species seems to be declining. Among all the ostracods listed in Table 2 , 12 species are endemic to the PA region: Candona quasiakaina Karanovic & Lee, 2012, Eucypris pigra (Fischer, 1851), Fabaeformiscandona alexandri (Sywula, 1981), F. myllaina Smith & Kamiya, 2007, Heterocypris auricularis Zhai & Zhao, 2014, H. vandouwei (Brehm, 1923), Ilyocypris innermongolica Zhai & Xiao, 2013, I.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations